Legal Position of Criminal Confiscation Against General confiscation in Bankruptcy for the Realization of Legal Certainty - Denny Chandra (GoAcademica Research & Publishing, 2022)
Law enforcement is an effort to revitalize legal norms. Where the law aims to create justice. In relation to general confiscation and criminal confiscation in bankruptcy, the law should give priority to the sense of justice in society, so that the law can be felt its usefulness which has an impact on compliance with the law. This study uses a statute approach, conceptual approach, and analytical approach. The results of the study indicate that there is no legal certainty in the case of general confiscation executions because of the length of time for a decision that has permanent legal force in criminal cases. Based on this, the author is of the view that the importance of harmonization of judicial institutions and the importance of reformulation and legal reconstruction in the case of confiscation in bankruptcy for the realization of legal certainty.